Proceedings of The 18th Indonesian Occupational Medicine Update (IOMU) 2026 - Occupational Medicine without Borders: Emerging Risks, Evolving Workforces, and Inclusive Collaboration - (Perhimpunan Kedokteran Okupasi Indonesia / PERDOKI), Indonesian Association of Occupational Medicin (Occupational and Environmental Medicine Journal of Indonesia, 2026)
This Supplemental Issue of the Occupational and Environmental Medicine Journal of Indonesia (OEMJI) compiles the scientific abstracts presented at the 18th Indonesian Occupational Medicine Update (IOMU) 2026, convened in Surabaya, Indonesia, from 15 to 17 May 2026. The IOMU has matured into the most prominent annual scientific platform of the Indonesian occupational medicine community, hosted by the Indonesian Association of Occupational Medicine Specialists (Perhimpunan Kedokteran Okupasi Indonesia / PERDOKI). Since its inception, the conference has served as a meeting point where clinicians, academics, industrial hygienists, regulators, employers, and worker representatives gather to translate emerging scientific evidence into preventive practice for the Indonesian workforce. The eighteenth edition reaffirms this tradition while expressly broadening its outlook to reflect a rapidly transforming global landscape. The theme of the 2026 conference, "Occupational Medicine without Borders: Emerging Risks, Evolving Workforces, and Inclusive Collaboration," was chosen in deliberate response to the realities reshaping work and worker health across Indonesia and beyond. Globalization of supply chains, rapid digitalization, the green and energy transitions, and post-pandemic labor reorganization have expanded the range of occupational risks. These include chemical hazards from new materials and processes, climate-related heat stress, re-emerging biological threats, and psychosocial pressures linked to artificial intelligence, hybrid work, and platform-based employment. At the same time, the workforce is undergoing significant changes. In some sectors, it is ageing, while in others it is becoming younger and more digitally oriented. The workforce is also increasingly female and more mobile. In low- and middle-income countries such as Indonesia, a large proportion of workers remain in the informal sector. Micro, small, and medium enterprises, along with gig workers, are key contributors to national productivity. However, they remain underserved by occupational health systems, which were largely designed for the formal industrial workforce of an earlier era. Addressing these challenges requires occupational medicine to work across sectors, disciplines, and both formal and informal settings. The abstracts in this issue reflect this approach. They include original studies, reviews, case reports, and policy analyses from academic institutions, industry, healthcare systems, and international collaborators. Key topics include AI-based surveillance, fatigue and psychosocial risk management, fitness-for-work assessments, ergonomic interventions in formal and informal sectors, climate and chemical exposure monitoring, and workplace mental health.The defining strength of this Supplemental Issue lies in its collaborative spirit. It brings together international keynote contributions, multi-institutional research from across the Indonesian archipelago, and emerging voices from postgraduate training programs. Through this approach, IOMU 2026 promotes an inclusive model of occupational medicine. In this model, scientific rigor, regulatory innovation, and field-level implementation reinforce one another. We express our sincere gratitude to PERDOKI for its sustained scientific leadership. We also thank all parties who support this event. Our appreciation extends to the international faculty who travelled to Surabaya, as well as to all authors, reviewers, and members of the scientific committee whose contributions made this volume possible. We hope that this collection not only reflects the current state of occupational medicine in Indonesia but also stimulates stronger cross-sectoral and cross-border collaboration. Such collaboration is essential to protect all workers—formal and informal, local and global—in an increasingly complex world of work.